Human capital of the child population and its selected determinants: Case study of Lviv city, Ukraine - Pantyley, Viktoriya (Bulletin of Geography. Socio-economic Series, 2017)
In conditions of modern economic and political destabilisation in Ukraine, human capital of the child population is considered as the most reliable indicator of socioeconomic development of the country and its regions. The primary goal of the study is the analysis of health status as the main element of human capital among the child population aged 014, and external and family environmental factors influencing this population group in the city of Lviv (in the light of available statistics and materials of the authors own sociological research). Research results show a potential crisis of human capital among the child population in Lviv city. Results of own field research show a statistically important correlation between the willingness of parents to have more children and the following independent variables: number of members in the household, and the households income. The state of health among the child population showed a significant correlation between the following variables: households income, life satisfaction among parents, availability of healthcare in the place of residence, financial affordability of healthcare, physical activity among children, influence of noise and unpleasant scents.